ANALYSIS DISASTER OF BOOKLET MEDIA OF PREPAREDNESS STUDENTS ABOUT DISASTERS IN SENIOR HIGH SCHOOL, SINGKAWANG CITY - Fajar Wulandari; Rien Anitra (GeoEco, 2018)
This study aims to determine the preparedness of high school students in dealing with natural disasters in Singkawang City, producing media booklet preparedness. Media booklet is an alternative for students in SMA 1, SMA 2 and SMA 6 for supporting learning, knowing the differences in learning outcomes and student response to the application of instructional media booklets material natural disaster mitigation and adaptation.This study uses research methods research and development, the steps taken include 4 resilience namely (1) define (2) design (3) develop (4) dessemiate is the definition, design, development, and dissemination.The research site is planned at Singkawang Senior High School in the even semester of 2017-2018 school year. The research design used purposive random sampling.  The subjects of this study were students of class XI of SMA in Singkawang, SMAN as many as 21 students. SMAN 2 as many as 28 students and SMAN 6 as many as 25 students.Quantitative data analysis with experimental methods and percentage techniques, data collection using preparedness and documentation questionnaires. Data analysis techniques used are anava tests. The prerequisite test used is normality test and homogeneity test.The results that validation by high school geography teachers reached a percentage of 84% and validation to expert media was 77%. Overall the results show that the learning device and media booklet can be used without revision. Hypothesis test results show a comparison of the probability value> 0.05 then Ho is accepted and the probability value <0.05 then Ho is rejected and if the value of sig (2-tailed) is 0.000 <0.05 then Ho is rejected which means the provision of media Booklet in the research has been affect the preparedness of Singkawang Senior High School students. The results of students' preparedness in dealing with disasters show high and very high preparedness values. As well as the combined index value included in the Ready category. The conclusion in this study is media booklet suitable for use in the teaching and learning process in the classroom. Media Booklet is effective in influencing and improving students' preparedness outcomes in dealing with natural disasters in Singkawang.